Clinical correlation of lymphovascular invasion and Silva pattern of invasion in early-stage endocervical adenocarcinoma: proposed binary Silva classification system - Stolnicu, Simona; Hoang, Lien; Almadani, Noorah; De Brot, Louise; Baiocchi, Glauco; Bovolim, Graziele; Brito, Maria Jose; Karpathiou, Georgia; Ieni, Antonio; Guerra, Esther; Kiyokawa, Takako; Dundr, Pavel; et al. (Pathology, 2022)
Silva invasion pattern can help predict lymph node metastasis risk in endocervical adenocarcinoma. We analysed Silva pattern of invasion and lymphovascular invasion to determine associations with clinical outcomes in stage IA and IB1 endocervical adenocarcinomas. International Federation of Gynecology and Obstetrics (FIGO; 2019 classification) stage IA-IB1 endocervical adenocarcinomas from 15 international institutions were examined for Silva pattern, presence of lymphovascular invasion, and other prognostic parameters. Lymph node metastasis status, local/distant recurrences, and survival data were compared using appropriate statistical tests. Of 399 tumours, 152 (38.1%) were stage IA [IA1, 77 (19.3%); IA2, 75 (18.8%)] and 247 (61.9%) were stage IB1. On multivariate analysis, lymphovascular invasion (p=0.008) and Silva pattern (p<0.001) were significant factors when comparing stage IA versus IB1 endocervical adenocarcinomas. Overall survival was significantly associated with lymph node metastasis (p=0.028); recurrence-free survival was significantly associated with lymphovascular invasion (p=0.002) and stage (1B1 versus 1A) (p=0.002). Five and 10 year overall survival and recurrence-free survival rates were similar among Silva pattern A cases and Silva pattern B cases without lymphovascular invasion (p=0.165 and p=0.171, respectively). Silva pattern and lymphovascular invasion are important prognostic factors in stage IA1-IB1 endocervical adenocarcinomas and can supplement 2019 International Federation of Gynecology and Obstetrics staging. Our binary Silva classification system groups patients into low risk (patterns A and B without lymphovascular invasion) and high risk (pattern B with lymphovascular invasion and pattern C) categories.
Keywords: Carcinoma; Adenocarcinoma; pattern of invasion; endocervical adenocarcinoma; Humans; lymphovascular invasion; Female; nádory děložního čípku; lidé; Lymphatic Metastasis; lymfatické metastázy; karcinom; Silva pattern; staging nádorů; ženské pohlaví; Retrospective Studies; prognóza; Uterine Cervical Neoplasms; adenokarcinom; retrospektivní studie; Neoplasm Staging; Prognosis; Stage